Neurological evaluation of newborn infants of mothers working in citrus groves in Northern Thailand - Winslow Joseph Borkowski (2018)
The purpose of this pilot study was to assess neurological function in newborn infants born to mothers working in citrus orchards in Northern Thailand for a period in excess of one year where pesticide applications average 35 times a year. Forty-one infants from uncomplicated term births at the community hospital in Fang, Thailand, were given neurological evaluations during the first four days of life. This was a cross-sectional study in which nine mothers worked in citrus orchards and 32 mothers did not. Examiners were not given the exposure history of the mothers. Twelve infants-five of them born to mothers from citrus orchards-had examinations demonstrating abnormal muscle tone. Using logistic regression, the final model showed that maternal citrus grove exposure and anesthesia use were significant predictors (p < 0.05) of abnormal muscle tone with adjusted odds ratios of 9.82 (CI=1.42, 68.07) and 5.99 (CI=1.003, 35.85) for exposure and anesthesia respectively.